A rapid non-destructive DNA extraction method for insects and other arthropods - Castalanelli, M.; Severtson, D.; Brumley, C.; Szito, A.; Foottit, R.; Grimm, M.; Munyard, Kylie; Groth, David (Elsevier, 2010)
Preparation of arthropods for morphological identification often damages or destroys DNA within the specimen. Conversely, DNA extraction methods often destroy the external physical characteristics essential for morphological identification. We have developed a rapid, simple and non-destructive DNA extraction technique for arthropod specimens. This technique was tested on four arthropod orders, using specimens that were fresh, preserved by air drying, stored in ethanol, or collected with sticky or propylene glycol traps. The technique could be completed in twenty minutes for Coleoptera, Diptera and Hemiptera, and two minutes for the subclass Acarina, without significant distortion, discolouration, or other damage to the specimens.